Development of conductive protein-based film reinforced by cellulose nanofibril template-directed hyperbranched copolymer. (1st June 2020) - Jin, Shicun; Li, Kuang; Gao, Qiang; Zhang, Wei; Chen, Hui; Li, Jianzhang
Graphical abstract: Highlights: Cellulose nanofiber-templated hyperbranched nanohybrids was prepared. Abundant active sites and architecture enabled high mechanical properties. The stress and toughness of the film increased by 362.1 % and 718.8 %, respectively. Integrated enhancement of strength and conductivity of composite were achieved. Abstract: Smart conductive soft materials prepared from natural polymers are arousing ever-increasing attention in numerous advanced applications. However, achieving the synergistic properties of high biocompatibility, mechanical performance, and conductivity remains a key challenge. Herein, a novel and green strategy is proposed to fabricate a soy protein (SP)-based composite by the incorporation of hyperbranched poly(amino ester)-pyrrole (HPPy) via in situ polymerization into a bio template of cellulose nanofibril (CNF). The formed HPPy@CNF nanohybrids not only serve as dynamic cross-linking sites to construct a strong and stable network, but also impart a remarkable conductive ability to biopolymer materials. The tensile stress and toughness of the modified SP-based film increased by 362.1 % and 718.8 %, respectively superior to those of previously reported reinforcing approaches. Moreover, this biopolymer film exhibited significantly improved electrochemical properties, water resistance, and thermal stability. This synthesis strategy is facile and eco-friendly and can be easily extended to other material systems.